The Impact of Place of Origin on International and Domestic Graduates' Mobility in China. Issue 1 (March 2022) - Zhai, Keyu; Moskal, Marta
This article addresses the cumulative effect of graduate migration and opportunities for career development. Using data from an online survey of 756 master's-level graduates educated in China and the UK, it examines their geographical mobility patterns and reveals significant differences between Chinese students who graduated from domestic universities and those who were educated abroad. Spatial autocorrelation analysis shows that international returnees, who usually had more privileged family backgrounds, clustered in China's highly developed core cities of the Bohai Economic Rim and Yangtze River Delta regions, such as Beijing and Shanghai, while domestic graduates tended to work and live in less affluent medium-sized cities around these regions. Women international graduates were more mobile than their men counterparts. Our results provide new evidence that draws attention to migration's role in graduate career development opportunities and highlights inherent economic discrimination within China, which is perpetuated by the national residency permit system — Hukou . The case of Chinese graduates shows that the mobility patterns of international and domestic graduates are influenced by and contribute to growing regional inequalities for career development in China.